Pengembangan Website Profil Desa Untuk Mendukung Digitalisasi Desa Berbasis Framework Laravel - Hartanti, Dyah Ayu Sri; Sujono, Sujono; Widya, Mohamad Anshori Aris; Samsudin, Samsudin; Rahman, Ade Nur; Andika, M Rio; Zuhrial, M. Adam (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
The Plosokerep Village Community Service Program (PKM) aims to provide an official website-based information medium and a digital promotion tool for local SMEs. The main issue is the absence of a village digital platform and limited promotion of SME products. The solution offered is the development of a Laravel-based Village Profile Website with features including a village profile, content management, an SME product showcase, and activity documentation. The implementation method comprises a needs analysis, system design, development, testing, and training for village officials. The results show that the website is fully functional, publicly accessible, and useful for information transparency and SME promotion. The presence of this website strengthens the village's digital identity while supporting a sustainable digitalization process.